An industrial quality control study on Elizardo Products, Inc. - Ramiscal, Edgar Allan S. (College of Engineering, 2005)
Elizardo Products Inc. (EPI) a part of the Elizardo Group of Companies (EGOC) is considered as one of the country's leading manufacturer of polyvinyl chloride (PVC), polyethylene, and polybutylene pipes, fittings and films. For over 25 years, EPI has manufactured these plastic products of highest quality, catering to the country's leading consumers and first-rate projects. In 1997, EPI, received its ISO 9002 certification, as it entered into the world market. This study aims to incorporate skills learned in Industrial Quality Control and make recommendations to help EPI establish statistical process control (SPC) over its processes, reduce process variability, and ultimately reduce costs incurred and further increase the company's quality standards. The statistical and mathematical tools and concepts learned throughout the course were used during the study. EPI was chosen as the subject of the study because of its newly installed management, and its goals to establish new process capability and process capability indices for fully automated processes of manufacturing rigid pipes, composing 80% of their total production. The company;s existing sampling procedures were also evaluated for their ability to monitor and screen the quality of their production process. Through frequent plant visits, interviews and on-site inspection of the production plant, significant data was gathered to recognize and identify the company's main quality related costs. With the management's help and statistical analysis tools, the proponents of the study were able to single out the company's foremost quality related problem, which is excessive material content in their rigid pipes. IT was realized from over 8 years of data, that on the average the company has been producing overweight pipes, meaning excess material has been incorporated into the production of each pipe, as compared to their standard weights for production. Also, the inspection and sampling procedures were evaluated for their in-process quality assurance. It was discovered that standard procedures for sampling were not precisely followed, and that the existing sampling plan was inept of assuring the conformance of their output to their high quality standards. Using the tools of SPC, the proponents intended to establish the capability of two extruder machines, used in manufacturing rigid pipes. It was known through years of experience and tests that three main quality characteristics affect excessive material usage namely, length, weight and thickness. Three machine settings on the other hand affect these quality characteristics, namely screw speed, haul-off and doing feeder. To estimate process capability, important assumptions have to be satisfied for the quality characteristics first which is the normality assumption. By studying the distribution of the three characteristics, it was found out that only the thickness satisfied this assumption, while the weight only slightly violated it. Using Shewhart control charts, process control was evaluated for these two quality characteristics, since this is the second important assumption needed for process capability analysis. Investigation of the charts revealed that the process was highly out of control, showing several out-of-control points and apparent cycles and trends. Thus, it was concluded that process capability analysis can not go further unless causes are assigned for these points and that they are eliminated to ensure that the process is subject only to chance causes of process variability, resulting to statistical control of the process.